The Effect of Digital Technology on the Operational Performance of MSMEs on E-Commerce Platforms Through the Mediating Role of Supply Chain Integration - Setyahadi, Ramadhani Naufal; Isfianadewi, Dessy (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the impact of digital technology on the operational performance of Micro, Small, and Medium Enterprises (MSMEs) on e-commerce platforms with supply chain integration mediation. The digital technologies referred to include the Internet of Things (IoT) and Artificial Intelligence (AI), which play a role in improving the efficiency and effectiveness of business processes. This study uses a quantitative approach with a survey method of 198 MSME players in Indonesia who run their businesses through e-commerce platforms. Data analysis was performed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method through SmartPLS software. The results show that digital technology has a positive impact on supply chain integration, both internally, with suppliers, and with customers. Supply chain integration has also been proven to have a significant impact on improving the operational performance of MSMEs. In addition, the supply chain integration variable acts as a mediator between digital technology and operational performance. These findings confirm that the application of digital technology supported by strong supply chain integration can drive increased efficiency, responsiveness, and competitiveness of MSMEs in the digital era.